2022
DOI: 10.1002/csc2.20764
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural carbohydrate content in the stubble per unit area regulates grain yield of the second crop in rice ratooning

Abstract: Rice (Oryza sativa L.) ratooning has attracted attention due to its higher yield potential. In the present study, a field experiment on rice ratooning using two rice genotypes, near isogenic line (NIL)-GN1A Takanari and Koshihikari, was conducted in 2019 and 2020 in southwestern Japan to obtain direct evidence for the role of stubble nonstructural carbohydrate (NSC) concentration and/or content per unit area on grain yield of the second crop and to determine the effectiveness of a gene producing more spikelets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…However, the number of filled spikelets did not differ between cutting heights in 2021 but was higher at low cutting height in 2022. The result in 2021 was in agreement with previous studies (Daliri et al, 2009;Ling et al, 2019;Nakano et al, 2020Nakano et al, , 2022Shahri et al, 2012).…”
Section: Grain Yield Of the Second Crop As Affected By Cutting Height...supporting
confidence: 92%
See 3 more Smart Citations
“…However, the number of filled spikelets did not differ between cutting heights in 2021 but was higher at low cutting height in 2022. The result in 2021 was in agreement with previous studies (Daliri et al, 2009;Ling et al, 2019;Nakano et al, 2020Nakano et al, , 2022Shahri et al, 2012).…”
Section: Grain Yield Of the Second Crop As Affected By Cutting Height...supporting
confidence: 92%
“…Several previous studies reported that stubble NSC content per unit area positively correlated with grain yield, the number of spikelets, and the number of panicles of the second crop (Nakano et al., 2020, 2022; Turner & Fund, 1993). Our recent study found that the lack of stubble leaf blade decreased grain yield by decreasing the number of spikelets, number of panicles, number of spikelets per panicle, percentage of filled spikelets, and 1000‐grain weight (Nakano et al., 2021).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…It has been considered that crop duration of ratoon crop is also regulated by stubble cutting and with low cutting height, crop duration can be extended ( Wang et al, 2020 ). Yang et al (2022) supported this theory, whereas studies from Japan and India had the opposite result ( Nakano et al, 2022 ; Lal et al, 2023 ). This could be also attributed to the varietal difference in adaptation to cutting height.…”
Section: Discussionmentioning
confidence: 91%